An exploration of nursing research perceptions of registered nurses engaging in research activities at a metropolitan hospital in Western Australia - Evans, G.; Duggan, Ravani; Boldy, Duncan (Elsevier BV, 2014)
AIM: To explore perceptions about nursing research of registered nurses (RNs) who were engaged in research activities at a metropolitan hospital in Western Australia. BACKGROUND: In order to improve RNs' research engagement and promote evidence-based practice, Nurse Research Consultants (NRCs) were appointed jointly by the study hospital and a local university. This joint appointment commenced in 2004 in the hospital's emergency department. Early findings indicated that the NRC role was effective in assisting registered nurses with research activities and hence the NRC role was expanded to all areas of the hospital. However, no formal investigation had been carried out to explore the effect of the NRC role on RNs' engagement with nursing research across the hospital. DESIGN: A qualitative interview process. METHODS: Ten RN participants from the adult and paediatric wards were interviewed. Audio-recorded data were transcribed verbatim and thematic analysis was undertaken. RESULTS: Four main themes were identified, namely: perceptions of nursing research, perceived enablers, perceived barriers and improving research engagement. There was some overlap with some sub-themes being linked with more than one theme. This appeared to be due to differing levels of research education and research engagement. CONCLUSION: 6pc some of the RNs that participated in this study were experienced in the conduct of research, finding adequate support from NRCs in the workplace, whilst others experienced barriers limiting their involvement in nursing research activities. These barriers could be reduced with additional education, support, improved communication, time and opportunities to undertake research activities.